The PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DAN PEMBERIAN REWARD TERHADAP KINERJA GURU: PERAN MOTIVASI GURU SEBAGAI VARIABEL MEDIASI - Josua Manik; Marlinda Siahaan (LP2M IAIN Sultan Amai Gorontalo, 2021)
This study aims to determine the effect of the principal's managerial skills and the provision of rewards on teacher performance through teacher motivation. This study uses a quantitative approach. The population in this study was 100 with a total sampling technique of sampling. The data in this study were processed using path analysis or path analysis assisted by the Smart PLS program. The results showed that partially managerial skills affect teacher performance as well as work motivation. Partially giving rewards also affect teacher performance and work motivation. Another result of the path analysis test found that indirectly motivation can affect the relationship between managerial skills on teacher performance as well as giving rewards to teacher performance. These results illustrate that the presence of good principal managerial skills and the provision of appropriate rewards can increase teacher motivation so that it also has an impact on maximum work results.